Handbook of reloading basics - Sharpless, Robin, frey50; Sapp, Rick (Iola, WI Krause Publication, 2014)
"With ammo shortages on retailer's shelves, unprecedented firearms sales across the country, and burgeoning numbers of new shooters, reloading is growing in leaps and bounds. Handbook of Reloading Basics, written by industry experts Robin Sharpless and Rick Sapp, is aimed squarely at the new handloaders and simplifies both the equipment and the process. Inside this bench-handy reference you'll find: Step-by-step instructions for reloading metallic cartridges and modern shotshells; Press selection--single-stage, turrets and progressives explained; Component breakdown--primers, cases, hulls, powder, wads and bullets; Dozens of illustrative photos and a comprehensive resource listing"--Page 4 of cover.
"Press setups for metallic cartridges and shotshells ; Step by step instructions and safety tips"--Cover.
Keywords: Handloading of ammunition; Handloading of ammunition